Solar Drying of Tropical Agricultural Crops: A Caribbean Perspective - Sankat, C K; Maharaj, R; Mujafar, S (Annals of Arid Zone, 2016)
Drying continues to be an important operation in the processing, preservation and. marketing of tropical agricultural crops. While" sun drying is still widely practiced, the use of solar dryers present a viable "alternative to counteract the disadvantages of sun drying, while offsetting the high costs associated with conventional drying systems. This review describes the various solar systems that have been" designed, built and tested to successfully dry a wide range of tropical c~ops. These include simple, low-cost natural convection cabinet and wire basket dryers suitable for small farmers/processors of both a direct and indirect type; cabinet dryers which incorporate separate air heaters and employing the natural and forced convection and larger, mixed-mode or hybrid dryers, that are more dependable and suitable "for industrial use; and dryers, which incorporate a supplementary oil and/or biomass burner so as to facilitate drying at nights or in periods of inclement weather. Converting the roofs of processing stations to provide solar heat for drying large volumes of crops is also described as a method. The drying of herbs,. fruits, cocoa, coconut, nutmeg, root crops, timber and fish along with drying curves and drying behavior are included. The processing considerations to enhance principally the quality and marketability of the dried product are noted. Given the imperative to integrate the drying process into the food processing chain, marketing and quality considerations are explored. Key word.,: Solar dryers, natural and forced convection, mixed mode, roof dryers, tropical commodities, drying behavior, pre-processing, quality, marketing.